Clean beauty - literature review of new trends in cosmetics - Célia Luiza Petersen Vitello Kalil; Artur Stramari de-Vargas; Flávia Pereira Reginatto Grazziotin; Valéria Barreto Campos; Christine Rachelle Prescendo Chaves (Sociedade Brasileira de Dermatologia (SBD), 2022)
In recent years, there has been an increasing trend toward the search for nature-friendly cosmetics without chemical or synthetic ingredients, thus boosting sales of products within this market niche. Currently, the term clean beauty refers to products that do not contain ingredients with unknown impacts on our bodies or that are potentially harmful to the environment. However, the definition of green beauty products, as well as vegan, natural, or organic products, is not regulated by ANVISA. Therefore, this study aimed to review these definitions to facilitate the medical understanding of the subject.